Broadband surface enhanced infrared absorption with multiple Fano resonance by metallic oblique-wire-bundle metamaterial absorbers - Hsueh-Shun Lee; Yu-Ping Kuang; Cheng-Yu Lu; Ta-Jen Yen; Tsung-Yu Huang (Scientific Reports)
Abstract Higher sensitivity with specific recognition of a sensor could ease the burden of sample purification or labelling procedure for specific testing and detection and there appear two methods including surface enhanced infrared absorption (SEIRA) and surface enhanced Raman scattering (SERS), promising better sensitivity and specificity, simultaneously, via detection of molecular footprints. Furthermore, researchers employ Fano resonance to further boost the detection limit of SEIRA by coupling between two absorption bands from molecules and metamaterials. Still, the current metamaterial absorbers are almost narrow band and require a specific design, only suitable for limited chemicals. Thus, in this work, we would like to design a broadband oblique-wire-bundle (OWB) metamaterial absorber (MA) which could interact with multiple functional groups’ absorption from a sample, thus easing the burden of custom-made resonators. In experiments, indeed, our designed OWB MA developed four Fano resonance responses with three PMMAs’ functional groups and one function group from carbon dioxide. The counterpart planar MA also performed SEIRA yet without occurrence of Fano resonance as a comparison. We believe this proposed OWB MA could facilitate the development of rapid detection in the field of food safety and chemical detection.